Progressive Effects of N-myc Deficiency on Proliferation, Neurogenesis, and Morphogenesis in the Olfactory Epithelium - Wittmann, Walter (Dev Neurobiol, 2014)
N-myc belongs to the myc proto-oncogene family, which is involved in numerous cellular processes such as proliferation, growth, apoptosis, and differentiation. Conditional deletion of N-myc in the mouse nervous system disrupted brain development, indicating that N-myc plays an essential role during neural development. How the development of the olfactory epithelium and neurogenesis within are affected by the loss of N-myc has, however, not been determined. To address these issues, we examined an N-myc(Foxg1Cre) conditional mouse line, in which N-myc is depleted in the olfactory epithelium. First changes in N-myc mutants were detected at E11.5, with reduced proliferation and neurogenesis in a slightly smaller olfactory epithelium. The phenotype was more pronounced at E13.5, with a complete lack of Hes5-positive progenitor cells, decreased proliferation, and neurogenesis. In addition, stereological analyses revealed reduced cell size of post-mitotic neurons in the olfactory epithelium, which contributed to a smaller olfactory pit. Furthermore, we observed diminished proliferation and neurogenesis also in the vomeronasal organ, which likewise was reduced in size. In addition, the generation of gonadotropin-releasing hormone neurons was severely reduced in N-myc mutants. Thus, diminished neurogenesis and proliferation in combination with smaller neurons might explain the morphological defects in the N-myc depleted olfactory structures. Moreover, our results suggest an important role for N-myc in regulating ongoing neurogenesis, in part by maintaining the Hes5-positive progenitor pool. In summary, our results provide evidence that N-myc deficiency in the olfactory epithelium progressively diminishes proliferation and neurogenesis with negative consequences at structural and cellular levels. © 2013 The Authors. Developmental Neurobiology Published by Wiley Periodicals, Inc. Develop Neurobiol 74: 643–656, 2014